DAMPAK MATAKULIAH METODOLOGI PENELITIAN DAN SEMINAR TERHADAP KEMAMPUAN MENULIS KARYA ILMIAH (SKRIPSI) SERTA KEMAMPUAN PRESENTASI MAHASISWA (STUDI KASUS MAHASISWA UNIVERSITAS DARMA PERSADA PRODI BAHASA DAN KEBUDAYAAN JEPANG) - fitri, zainur; Nursari, Bertha (Universitas Pakuan, 2024)
The aim of this research is to evaluate the influence of Research Methodology Courses and History, Culture and Society Seminars on students' abilities in writing scientific papers (thesis) and presentations at the Darma Persada University Japanese Language and Culture Study Program. This research has a quasi-experimental design with a One Group Pre-test and Post-test approach. The research participants consisted of 41 Fourth Level Students of the Japanese Language and Culture Study Program at the Faculty of Language and Culture, Darma Persada University in the 2022/2023 Academic Year, with details of 28 male students and 13 female students. The research results revealed that the Research Methodology Course and Seminar on Japanese History, Culture and Society had a positive impact on students' ability to write a thesis and make presentations. This can be seen from the significant difference between the mean UTS and UAS scores. The average UTS score was 74.61, which then increased to 81.05 in the UAS, showing significant improvement. Apart from that, the results of the questionnaire also show that the majority of students gave a positive response to this course. They feel that this course provides great benefits in helping improve their academic skills.